Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan Bagian Pabrik Unit Produksi Pagilaran PT Pagilaran - Muhamad Yazid Bustomi; Lestari Rahayu Waluyati (Jurnal Ekonomi Pertanian dan Agribisnis, 2019)
The objectives of this study were (1) to find out the effects of leadership style and work environment on employee work satisfaction, (2) to analyze the effects of leadership style and work environment on organizational commitment, and (3) to identify the effects of leadership style, work environment, work satisfaction, and organizational commitment on employee performances of tea processing at Pagilaran Production Unit of PT Pagilaran. The sampling technique used stratified random sampling method with a total of 112 respondents from a total of 156 employees working in the tea processing factory. The data analysis method was SEM-PLS with SmartPLS version 3.0 software to see the effects of exogenous latent variables (leadership style and work environment) on endogenous latent variables, i.e. job satisfaction, organizational commitment, and employee performance. The evaluation result of the outer model indicates that the Average Variance Extracted (AVE) value for all variables is greater than 0.5 and the composite reliability value is greater than 0.6. It states that the model used in this study is acceptable, while the evaluation of inner model based on the bootstrapping test shows that leadership style variables and work environment have  positive effects on work satisfaction and organizational commitment, but do not have direct effects on employee performances. The work satisfaction variables do not have significant effects on the employee performances, while organizational commitment has direct effects on the employee performances of tea processing at the production unit